Kebijakan Hukum Pidana Terhadap Penjualan E-Book Bajakan Melalui Marketplace - Tharob, Khusnul; Hehanussa, Deassy Jacomina Anthoneta; Taufik, Iqbal (Faculty of Law Universitas Pattimura, 2025)
Indonesia is one of the four countries with the highest piracy rate in the world. After software and music piracy, book piracy ranks third. Violations of books are increasingly occurring through reproductions, innovations and traditional works, as well as violations of works when other parties do not exercise the same rights. Author's rights, including the exclusive rights of the author. Apart from that, it could be considered a violation of the book owner's rights if another party reproduces the book. in amounts without transfer or Limitation. Increased buying and selling of books copied by other people who are not copyright holders is available on e-commerce platforms. Accelerating the fair use of law and technology in protecting copyright holders is very necessary. Apart from providing legal protection for copyright holders. The research results show that: (1) Selling pirated e-books through the marketplace can be qualified as a criminal act. Under the law in many countries, including Indonesia, this action violates copyright. Pirated e-books are works that are distributed without permission from the copyright holder. This violates existing Copyright Laws in many jurisdictions, including Indonesia; (2) As regulated in Article 10 of the Copyright Law, the management site is responsible for any copyright infringement that occurs in the site it manages. So, based on this, the marketplace can be held accountable in the event of a copyright violation in the form of a literary work (E-book) on the marketplace's platform. In the event of a violation of a literary work, the creator/copyright holder or their heirs can report/sue the seller and marketplace through litigation and non-litigation channels. However, in litigation efforts in the form of criminal proceedings, the enactment of the complaint offense makes legal action increasingly narrow.